PERANCANGAN MEDIA APLIKASI BUS TRANS METRO BANDUNG - Sheila Christy; Roy Anthonius Susanto (Serat Rupa: Journal of Design, 2019)
Bandung as one city that has a dense population requires mobilization to carry out daily activities. In carrying out this mobilization, the community can choose to use private transportation or public transportation that has been provided by the government. Trans Metro Bandung (TMB) is one of the public transportation provided by the government with adequate facilities, but the majority of people find it difficult to obtain information about TMB buses, both routes, schedules, bus stops, and bus facilities. This can be overcome through media technology that can make it easier for people to get and interact with that information.The purpose of this design is to make it easier for people to find all information about TMB buses through informative and structured application media, having local characteristics that are tailored to the needs of the people of Bandung City. The design is emphasized on the element of User Experience and User Interface approach which ultimately aims to make it easier for people to find information related to TMB facilities that are integrated in 1 digital application.